Performance of Hevea clones in Assam - Mondal G C; Deka H K; Gohain T; Gupta C; Krishna Das; Mondal D; Singh R P; Thapliyal A P (Indian Journal of Natural Rubber Research, 1999)
Growth and initial yield of ten Hevea clones were studied under the agroclimatic conditions of Assam in North East India. RRIM 600 exhibited the highest girth in juvenile stage closely followed by PB 235 and RRII 118. At the immature stage, PB 235 showed the highest girth after the commencement of tapping during mature stage also, closely followed by PB 86 and RRII 118. Poor growth as well as low rubber yield was observed in all the ten clones during winter months characterised by low temperature from December to March combined with the wintering and refoliation stresses. High DRC of latex, low dry rubber yield and gigh plugging index were observed in all ten clones during May to August. An increasing trend in the yielding pattern was observed from August onwards in all the clones with a maximum in November. RRIM 600 had the highest yield for the first three years of tapping followed by RRII 105 and PB 235 with minimum in GI 1.
Keywords: Assam; Climate; DRC; Growth; Hevea clones; North East India; Plugging index; Yield